The role of metalloporphyrins on the physical-chemical properties of petroleum fluids. (15th January 2017) - Santos Silva, Hugo; Sodero, Ana C.R.; Korb, Jean-Pierre; Alfarra, Ahmad; Giusti, Pierre; Vallverdu, Germain; Bégué, Didier; Baraille, Isabelle; Bouyssiere, Brice
Abstract: The presence of metalloporphyrins in crude oil has been known by many years now but their role on the physical-chemical properties of petroleum fluids, such as the aggregation of the high-molecular weight phases, remains unknown. In this paper, these properties are studied using different molecular modeling techniques (Molecular Dynamics, Semi-empirical PM7 and Density Functional Theory). This combined methodology allowed us characterizing the nature of these interactions, how it dominates the electronic structure of the stacked molecules and what is their participation on the formation of the nano-, micro- and macro-aggregates.